2006
DOI: 10.2193/0022-541x(2006)70[554:hsbrwi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Selection by Recolonizing Wolves in the Northern Rocky Mountains of the United States

Abstract: Gray wolf (Canis lupus) populations have persisted and expanded in northwest Montana since 1986, while reintroduction efforts in Idaho and Yellowstone have further bolstered the regional population. However, rigorous analysis of either the availability of wolf habitat in the entire region, or the specific habitat requirements of local wolves, has yet to be conducted. We examined wolf‐habitat relationships in the northern Rocky Mountains of the U.S. by relating landscape/habitat features found within wolf pack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 28 publications
2
104
0
Order By: Relevance
“…Stephenson (1974*) found a much steeper average slope of 33 degrees in the Brooks Range of Alaska. Using elevation and slope measured in a GIS model, Oakleaf (2002) found core areas of pack home ranges in the northern Rocky Mountains at lower elevations with gentler slopes. Although we found that most dens were located within home range core areas, we found no significant correlation between den sites and elevation or slope.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stephenson (1974*) found a much steeper average slope of 33 degrees in the Brooks Range of Alaska. Using elevation and slope measured in a GIS model, Oakleaf (2002) found core areas of pack home ranges in the northern Rocky Mountains at lower elevations with gentler slopes. Although we found that most dens were located within home range core areas, we found no significant correlation between den sites and elevation or slope.…”
Section: Discussionmentioning
confidence: 99%
“…We selected six variables that previous literature suggested were important in habitat selection by Wolves (Matteson 1992;Mladenoff et al 1995;Oakleaf 2002) and that could be generated in ArcView from existing data layers (Table 2).…”
Section: Coarse-scale Habitat Selection Using Remotely-sensed Data Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolves, on the other hand, disperse widely (Fritts, 1983;Lehman et al 1992;Forbes & Boyd, 1997), possibly an adaptation to avoid inbreeding as unlike bears or caribou, wolves are territorial. This dispersal ability has allowed wolves to recolonize many patches of suitable habitat across western North America where they had been eliminated by predator control (Hayes & Gunson, 1995;Oakleaf et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In advance of developing RSF models for wolves, we assembled Geographic Information Systems (GIS) layers of landscape characteristics ( Table 2.1) that we hypothesized would influence wolf selection based on previous wolf-selection studies (Arjo and Pletscher 2004, Kuzyk et al 2004, Oakleaf et al 2006, Milakovic et al 2011. We classified the landscape into vegetation classes using multispectral images from SPOT 4/5 satellites (available at www.geobase.ca).…”
Section: Selection Of Landscape Features By Wolvesmentioning
confidence: 99%